Don Juan Goes Online: the Functioning of a World-Literature Figure in Internet Conditions - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article is a continuation of discussions about the changes that the literary image of Don Juan undergoes at present in online literature. Appealing to literary classics is quite common in the works of Internet authors. Intertextuality seems to be one of the writing strategies on the web. The subject of our interest are the works referring to the literary image of Don Juan published on Russian literary websites, not included in the offline process and overlooked by literary critics. The main task has been to identify the leading tendencies in creating the image of Don Juan, as well as the results to which employing them led. Analyses of a group of texts belonging to online literature allow the author of the paper to comment on the ways in which a literary image born in the Spanish literature of the 17th century continues to exist in the peculiar Internet conditions.